2004
DOI: 10.1128/aac.48.11.4488-4490.2004
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Simultaneous Splenic Sample PCR with Blood Sample PCR for Diagnosis and Treatment of Experimental Ehrlichia canis Infection

Abstract: This report presents evidence that dogs recover from acute canine monocytic ehrlichiosis (CME) after 16 days of doxycycline treatment (10 mg/kg of body weight every 24 h). Blood PCR was as valuable as splenic aspirate PCR for early diagnosis of acute CME. Splenic aspirate PCR was, however, superior to blood PCR for the evaluation of ehrlichial elimination.Canine monocytic ehrlichiosis (CME) is a tick-borne disease with a global distribution (9). Diagnosis of CME is confirmed by demonstration of morulae in bloo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

7
101
2
15

Year Published

2008
2008
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 92 publications
(125 citation statements)
references
References 16 publications
7
101
2
15
Order By: Relevance
“…Secondly, considering that the nested-PCR technique utilized in this study is highly sensitive and specific (WEN et al, 1997;MURPHY et al, 1998), the test's capacity to detect the presence of Ehrlichia DNA in soropositive dogs will depend on the type of sample collected for the test. In the acute phase, Ehrlichia can be easily detected in blood, while in subclinical and chronic phases, the tissues most appropriate for sampling are the spleen and bone marrow, respectively (HARRUS et al, 1998a,b;HARRUS et al, 2004;MYLONAKIS et al, 2004). Considering that in the present study only blood samples were utilized for nested-PCR, it is possible that dogs in subclinical and chronic clinical phases could not be correctly diagnosed.…”
Section: Discussionmentioning
confidence: 85%
“…Secondly, considering that the nested-PCR technique utilized in this study is highly sensitive and specific (WEN et al, 1997;MURPHY et al, 1998), the test's capacity to detect the presence of Ehrlichia DNA in soropositive dogs will depend on the type of sample collected for the test. In the acute phase, Ehrlichia can be easily detected in blood, while in subclinical and chronic phases, the tissues most appropriate for sampling are the spleen and bone marrow, respectively (HARRUS et al, 1998a,b;HARRUS et al, 2004;MYLONAKIS et al, 2004). Considering that in the present study only blood samples were utilized for nested-PCR, it is possible that dogs in subclinical and chronic clinical phases could not be correctly diagnosed.…”
Section: Discussionmentioning
confidence: 85%
“…However, the detection of the agent can decrease at this site with the progression of infection or the treatment of bacteraemia compared to other sites (HARRUS et al, 2004;BANETH et al, 2009) The absence of apparent clinical signs and the long duration of the subclinical stage may hinder the detection of infection (HARRUS & WANER, 2011;WANER & HARRUS, 2013), likely represented in this study by the asymptomatic group. HARRUS et al (1998) observed the increased detection of E. canis in spleen samples in the subclinical stage, and in blood and bone marrow in the acute phase, whereas the number of positive animals detected by PCR using blood and spleen samples was similar (HARRUS et al, 2004). However, spleen samples are not routinely Table 2 -DNA detection of E. canis using nested PCR in the buffy coat and bone marrow compared to clinical signs observed in dogs in Várzea Grande, Mato Grosso.…”
Section: Discussionmentioning
confidence: 79%
“…Este mesmo animal apresentou PCR de amostra de baço positiva nos dias 10 e 14. Isso sugere que a amostra de sangue total não é a melhor escolha para a pesquisa de E. canis por PCR 38 , de modo que a melhor opção de amostra para PCR pós-tratamento, a fim de avaliar a eliminação da bactéria, seria do baço porque este órgão alberga Ehrlichia por mais tempo. Em nosso estudo, optamos por empregar a nested PCR em amostras de sangue obtidas antes do tratamento devido à aplicabilidade deste método de coleta e sua praticidade na rotina da clínica veterinária de pequenos animais.…”
Section: Discussionunclassified
“…No pós-tratamento, optou-se pela punção de baço. Contudo, os próprios autores afirmam que a alta sensibilidade da PCR torna as duas formas de amostragem semelhantes 38,39 . O animal T2 apresentou resultado negativo na PCR de amostra de baço no dia 14.…”
Section: Discussionunclassified